(untitled) (LACCEI, 2024)
This research was carried out in order to analyze the characteristics of the sales process and the aspects of the SCRUM methodology that should be considered to propose a web application design in the city of Trujillo. The type of study was intentional calculating 45 service companies as a sample. A questionnaire was used to collect data. In addition, for the design of the proposal, the web application based on information symmetry was used as a theoretical framework. The dimensions of the factual variable were sales and customers, while the propositional axes considered in the propositional variable were security and usability. Likewise, the thematic axes on which the thematic variable was analyzed were roles, events and artifacts. The results show that "Effectiveness in sales made", "Execution of the sales process", "Customer acquisition" and "Customer recurrence" had an average "regularly" score of 49%, 49%, 36% and 29%, respectively. Having said all the above, it can be concluded that there is a deficiency in the sales processes the indicator with the lowest score is "Customer Recurrence", which is why a web application was developed based on the symmetry of information for service companies in the city of Trujillo.